Methodological Possibilities of Spiritual and Ethical Education in The Process of Globalization - Jumayeva Mahbuba Oktam's Qizi (Euro Asian Journal Publishing, 2024)
In this article, the issue of knowledge and moral values serving as an important factor in the formation of the spirituality of young people in achieving sustainable development of our country is reflected.
Keywords: Spirituality; threat; globalization